Evaluation of Two Chemiluminescent and Three ELISA Immunoassays for the Detection of SARS-CoV-2 IgG Antibodies: Implications for Disease Diagnosis and Patients’ Management - Speletas, Matthaios; Kyritsi, Maria A.; Vontas, Alexandros; Theodoridou, Aikaterini; Chrysanthidis, Theofilos; Hatzianastasiou, Sophia; Petinaki, Efthimia; Hadjichristodoulou, Christos (Frontiers in Immunology, 2020)
The estimation of anti-SARS-CoV-2 IgG antibodies is possibly the best approach to accurately establish the number of infected individuals and the seroprevalence of COVID-19 within a population. Thus, several commercial immunoassays have recently been developed. The purpose of our study was to assess the performance of five commonly used immunoassays in Greece (3 ELISA, namely Euroimmun SARS-CoV-2, GA GENERIC SARS-CoV-2 and Vircell COVID-19; and 2 chemiluminescent, namely ABBOTT SARS-CoV-2 and ROCHE Elecsys Anti-SARS-CoV-2 test) for the detection of anti-SARS-CoV-2 IgG antibodies. Sera specimens derived from 168 individuals were utilized to assess the specificity and sensitivity score of each assay. Among them, we included 99 COVID-19 patients (29 asymptomatic, 36 with symptom onset 4-14 days before serum sampling, and 34 with symptom initiation ≥ 15 days ago), and 69 volunteers with sera specimens collected prior to the SARS-CoV-2 outbreak and maintained at -80⁰C. We demonstrated that chemiluminescent immunoassays exhibit a significantly higher specificity score but a lower sensitivity, compared to ELISA immunoassays. Moreover, immunoassays detecting IgG antibodies against SARS-CoV-2 N protein instead of S protein alone are more reliable, considering both specificity and sensitivity scores. Interestingly, all asymptomatic patients displayed anti-SARS-CoV-2 IgG antibodies, confirmed by at least two immunoassays. We suggest that chemiluminescent assays could be used as screening methods for the detection of anti-SARS-CoV-2 antibodies to evaluate with greater accuracy the prevalence of disease in the general population, while ELISA assays would be more reliable to evaluate, and follow-up confirmed COVID-19 patients